Leading with values : strategies for making ethical decisions in business and life - Malhotra, Neil Ankur; Shotts, Kenneth W. (Cambridge : Cambridge University Press, 2022)
As societies become more polarized, there is increasing pressure for business leaders to have a sense of purpose and to make moral decisions. Being a good leader requires both a keen understanding of the realities of human decision making as well as an analysis of what is right and wrong. This book integrates lessons from three intellectual traditions - psychology, philosophy, and political economy - to guide readers on a journey to rigorously explore their values and decision making. The authors begin by examining people's intuitions about right and wrong. They then clarify principles that embody these intuitions and help readers engage with others whose intuitions or principles differ from their own. Ultimately, this book teaches readers how to be strategic as they lead with their values: as individuals, as designers of organizations, and as businesspeople interacting with societal institutions.
Follow Your Gut? -- Self-Deception and Rationalization -- The Power of the Situation -- Shareholders, Stakeholders, and Societal Institutions -- Weighing Consequences -- Perspective-Taking -- Being Fair -- What Are Your Core Values?
Title from publisher's bibliographic system (viewed on 28 Jan 2022).
Keywords: Business ethics; Values; Leadership -- Moral and ethical aspects